SUSTAINABILITY DIRECTIVE STRATEGY OF ECOLOGYCAL IN THE FACE OF THE SURGE IN THE COVID-19 PANDEMIC AND OTHER PANDEMICS - Maya Dewi Dyah Maharani; Tatan Sukwika (Sustainable Environmental and Optimizing Industry Journal, 2022)
The World Health Organization (WHO) said that the COVID-19 pandemic is a disease caused by the new coronavirus SARS-CoV-2 (Severe Acute Respiratory Syndrome - Coronavirus - 2) on March 11, 2020. The threat of the COVID-19 pandemic is revealed not only by the number of people infected and who experience death, but also especially for vulnerable people in populations that are most likely to be potentially infected. SARS-CoV-2 is a new virus in which the human population has no immunity. The research was conducted in Bogor, West Java province at the end of December 2019, followed by 2020 until February 2021. The analysis used is SWOT (Strengths, Weaknesses, Opportunities, Threats). The internal and external factors included in swot analysis are leverage attributes of mitigation ecological sustainability processing that use Multi Dimensional Scaling (MDS), leverage and Monte Carlo analysis. The formulation of the resulting directive strategy in ecological sustainability mitigation in the face of the surge of Covid-19 and other pandemics is the improvement of echo-ethics through the implementation of One-Health. The strategy is built from internal weakness factors, namely the implementation of echo-ethics which is a leverage attribute with a Root Mean Square (RMS) value of 2.98. While the external factor of opportunity is the application of One-Health which is a leverage attribute with RMS of 2.90.